Advances in understanding the surface chemistry of lignocellulosic biomass via time‐of‐flight secondary ion mass spectrometry. Issue 1 (12th December 2016) - Tolbert, Allison; Ragauskas, Arthur J.
Abstract: Overcoming the natural recalcitrance of lignocellulosic biomass is necessary in order to efficiently convert biomass into biofuels or biomaterials and many times this requires some type of chemical pretreatment and/or biological treatment. While bulk chemical analysis is the traditional method of determining the impact a treatment has on biomass, the chemistry on the surface of the sample can differ from the bulk chemistry. Specifically, enzymes and microorganisms bind to the surface of the biomass and their efficiency could be greatly impacted by the chemistry of the surface. Therefore, it is important to study and understand the chemistry of the biomass at the surface. Time‐of‐flight secondary ion mass spectrometry (ToF‐SIMS) is a powerful tool that can spectrally and spatially analyze the surface chemistry of a sample. This review discusses the advances in understanding lignocellulosic biomass surface chemistry using the ToF‐SIMS by addressing the instrument parameters, biomass sample preparation, and characteristic lignocellulosic ion fragmentation peaks along with their typical location in the plant cell wall. The use of the ToF‐SIMS in detecting chemical changes due to chemical pretreatments, microbial treatments, and physical or genetic modifications is discussed along with possible future applications of the instrument in lignocellulosic biomass studies. Abstract : Understanding the surface chemistry of lignocellulosic biomass through ToF‐SIMS spectra and images. Summary of chemical, biological, and genetic modified biomass surface chemistry. Overview of different sample preparation techniques and how to analyze ToF‐SIMS spectra in relation to key lignocellulosic biopolymers.